Assessing Berry Number for Grapevine Yield Estimation by Image Analysis: Case Study with the Red Variety “Syrah” - Attinà, Giorgia (2022)
Mestrado em Engenharia de Viticultura e Enologia (Double degree) / Instituto Superior de Agronomia. Universidade de Lisboa / Faculdade de Ciências. Universidade do Porto